Service Design Thinking: A Case Study on Academic Lectures Addressed to Higher Education Students - Ivan Traina; Antonio Fracasso (New Ideas Concerning Science and Technology Vol. 10, 2021)
This chapter provides suggestions for developing and implementing academic lectures on Service Design Thinking addressed to students of Higher Education Institutions (HEI), based on a case study carried out at the Department of Education Studies of University of Bologna. It reports some advice and tips for teaching this new concept. Also, it points the attention on some aspects raised during the delivery of lectures in classroom that deserve to be shared with the growing community of professionals interested in this concept. This contribution focuses mainly on practical aspects that should be considered when organizing lectures on this theme. Therefore, the chapter consists of three sections: Presentation of innovative pedagogic approaches adopted to define a theoretic framework of reference. Provision of literature’s sample analyzed and used for developing lectures. Reflection about lessons learnt. This work is a collection of practical implication and feedback emerged during the experience carried out and it is aimed at stimulating a wide confrontation in order to find practices that can help to understand “how and what” to teach about Service Design Thinking in HEI context.